EFEKTIFITAS PEMBERIAN KONSELING TERHADAP TINGKAT KECEMASAN PASIEN PRA OPERASI SECTIO CAESAREA DI RUMAH SAKIT BHAYANGKARA WATUKOSEK - Dyah Siwi Hety (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
This research used pre pre test & post test design. Variable that is the effectiveness of counseling and patient anxiety levels pre SC operation. The population were all mothers who will be birthing in a hospital surgical SC Bhayangkara Watukosek. This study was conducted on 10 to 23 juli 2012, sampling techniques in a way accidental sampling, so we get a sample of 35 men and statistical tests used a statistical test Wilcoxon Signed Rank Test. The results obtained from 35 respondents, indicated that 26 respondents (74.3%) experienced anxiety before being given counseling before the operation and as many as 24 respondents (68.6%) experienced mild anxiety after being given counseling. Results of statistical test Wilcoxon Signed Rank Test using SPSS, the result shows ρ = 0.000 α = 0.05 which is well known ρ < 0.05, which means that there is effective provision of counseling to the patient's anxiety levels pre SC operations in Bhayangkara Watukosek Hospital 2012. Results of data analysis in this research note that - average respondent was experiencing anxiety before their counseling. Anxiety respondents are influenced by education, occupation and learned coping. Respondents who have higher levels of education, work and included in multipara will be able to provide a more rational response when compared with respondents who have low education, not working and are included in the primipara.Conclusions from this study are that counseling is an effective way to overcome the anxiety level in patients who will undergo surgery SC. Health workers are expected willing to provide good counseling to patients pre SC operation to avoid anxiety and occurs not only pay attention to the informed concent alone.